Adsorção de azul de metileno em biocarvão do endocarpo do fruto do ouricuri (Syagrus coronata (Mart) Becc.) reativado por reação de fento - Lima, Renata Silva de (2017)
The present work aims to evaluate the efficiency of the adsorption process using as adsorbent the biochar of the endocarp of Ouricuri, one of the main native palm trees of the Brazilian semi-arid region. The biomass was produced by the thermal decomposition of the biomass under vacuum and at relatively low temperatures, being used in this study the pyrolysed carbons at temperatures of: 400ºC, 600ºC and 800ºC. In order to evaluate the biochar, tests of adsorption of the methylene blue dye were carried out in function of variables such as time, grain size and pyrolysis temperature of the adsorbent. Biocharcoal were used without chemical treatment. The evaluation of the adsorption process of each material was determined by spectroscopy in the visible region (maximum Absortion of 665 nm), achieving around 96% removal of the methylene blue dye. Through the experimental design 23, it was possible to analyze that the variable with the greatest influence on the adsorption process was the mass of the adsorbent, followed by grain size. The response surface generated showed that the highest adsorption capacity of the methylene blue dye was 99.4% obtained for the 4.8 g level of the adsorbent, 800 ºC and granulometry of <0.149 mm. From the best condition in the experimental planning, the kinetic study was performed, where the results presented better fit for the pseudo model Second order. The adsorption isotherms followed the Redlich-Peterson model. In the regeneration of the coal by the Fenton oxidation, it led to a recovery of 19.31% of the adsorption capacity. The biocarbon was characterized by FTIR, DRX, TGA, and EDX techniques. In this way it was possible to conclude that the biocarbon of the endocarp of the Ouricuri is very efficient for the adsorption of dyes such as methylene blue, but that the regeneration of the coal through the reaction of Fenton presents low efficiency in studied conditions.